Effects of histamine on the development of MNU-induced mammary tumours - Faustino-Rocha AI, A. I. (2016)
Objective: Breast cancer is frequently diagnosed worldwide. Histamine acts as mediator in several cancers. Ketotifen is a mast cells stabilizer drug that inhibits their degranulation. This work aimed to evaluate the effects of histamine on the development of MNU-induced mammary tumors. Methods: Procedures followed the European Directive 2010/63/EU. Twenty animals were equally divided into two experimental groups: ketotifen and control. At seven weeks of age, all animals received an intraperitoneal injection of N-methyl-N-nitrosourea (MNU). Animals from ketotifen group received ketotifen in drinking water (1mg/Kg; 7days/week; for 18 weeks). At the sacrifice, mammary tumors were fixed and histologically evaluated. Results: During the protocol one ketotifen-treated animal died. At the end, eight animals from ketotifen group developed 19 mammary tumors (2.4 tumors per animal), while six animals from control group developed 21 mammary tumors (3.5 tumors per animal). Animals from control group developed one benign lesion and 20 non-invasive carcinoma; all lesions from ketotifen-treated animals were malignant, however they did not develop any comedo carcinoma that was the lesion of the highest grade of malignancy found in this work. Conclusion: Inhibition of histamine release by ketotifen seems to reduce the number and malignancy of MNU-induced mammary tumors.